The Messiah of Shiraz: Studies in Early and Middle Babism by Denis MacEoin (Leiden: Brill, 2009. 738 pages.) (American Journal of Islam and Society, 2009)
The book under consideration deals with Babism and Shaykhism, two religiousmovementsof nineteenth-century Iran.According toMacEoin, they areprincipally of note in that they were the precursors of the Baha’i faith. Thebook consists of the author’s Ph.D. thesis on the emergence of Babism from Shaykhism (completed in 1979, 250 pages); nine articles subsequently publishedin various journals and books, mainly on different aspects of Babism;seven articles written for the Encyclopedia Iranica; a conference paper; andthe author’s translation of the first one-and-a-half chapters of the Bab’sPersian-language Bayan. Almost all of this material is available on-line (forthe Ph.D. thesis, see www.h-net.org/~bahai/diglib/books/K-O/M/maceoin/FROMSHAYKHISMTOBABISM.pdf). As such, this book does not constitutenew research and must be regarded more as a retrospective on one scholar’swork. This leads to two questions: For whom is this work intended andhow should one review such a book – should one evaluate it on the basis ofthese works’ value at the time they were published or now? ...